Pseudotautological Question-Answer Unity in Russian Dialog: National Conditioning of the Models of Phatic Communication - I. A. Kuznetsov (Научный диалог)
Nationally determined models of phatic question-answer unities in the speech practice of native Russian speakers are considered. Particular attention is paid to the so-called pseudo-tautological question-answer unities of the type: - Where did you come here from? // - From there .... The question is raised about combining, when actualizing these unity, in speech, regulatory and metacommunicative functions. Two varieties of pseudotautological unity have been established: the response line in form corresponds to the initial interrogative (lexically and / or grammatically, phonetically, etc., cf. where - there, who - what , etc.); the response line in form repeats the initial interrogative line - in whole or in part. It is shown that in pseudotautological unities a special kind of pragmatic connection is realized - implicit, in which the initial and response lines are based on the appeal to conditions of success, presuppositions and presumptions, discourse implications, etc. It is concluded that the functioning of the phatic pseudotautological question-answer unities in the Russian dialogical discourse has a significant national conditionality: the emphasis in speech interaction is inevitably transferred to the interpersonal relations of the participants in the dialogue, to the value of communication in Russian speech practice.